2018
DOI: 10.31768/2312-8852.2018.40(4):309-314
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 Gene Polymorphism Is Associated With Breast Cancer in Iranian Patients

Abstract: Aim: Breast cancer (BC) is one of the leading causes of cancer death among women. Recent studies have characterized FoxP3 as a marker of regulatory T cells and an X-linked tumor suppressor gene, which is involved in the pathogenesis of BC. Therefore, we investigated the potential influence of three single-nucleotide polymorphisms (SNPs) of FoxP3 gene on the development of BC in Iranian women. Materials and Methods: The association between FoxP3 rs2232365, rs3761548 and rs4824747 polymorphisms and BC risk was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Genetic polymorphisms in FOXP3 may alter FOXP3 functionally or quantitatively, thereby modulating disease risk [ 26 ]. SNPs in FOXP3 gene have been detected in various cancers, for example, prostate cancer [ 16 ], colorectal cancer [ 17 ], breast cancer [ 18 ], gastric adenocarcinoma [ 19 ], thyroid cancer [ 20 ], non-small cell lung cancer [ 21 ], endometrial cancer [ 22 ], and cervical cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic polymorphisms in FOXP3 may alter FOXP3 functionally or quantitatively, thereby modulating disease risk [ 26 ]. SNPs in FOXP3 gene have been detected in various cancers, for example, prostate cancer [ 16 ], colorectal cancer [ 17 ], breast cancer [ 18 ], gastric adenocarcinoma [ 19 ], thyroid cancer [ 20 ], non-small cell lung cancer [ 21 ], endometrial cancer [ 22 ], and cervical cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human FOXP3 gene is mapped to the X chromosome at Xp11.23, and has been confirmed to have numerous SNPs in the exon, intron, and promoter regions [ 10 , 15 ]. Previous studies on different ethnic groups have shown that polymorphisms in the FOXP3 gene are associated with the development of various cancers, such as prostate cancer [ 16 ], colorectal cancer [ 17 ], breast cancer [ 18 ], gastric adenocarcinoma [ 19 ], thyroid cancer [ 20 ], non-small cell lung cancer [ 21 ], endometrial cancer [ 22 ], and cervical cancer [ 23 ]. To date, only one study has investigated the underlying role of two FOXP3 promoter region SNPs (rs3761549 and rs2280883) in the progression of HCC in a Chinese population [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…DUSP9, FLNA, GPC3, RBBP7, KDM6A, RBMX, FOXP3, and EDA2R mutation patterns are among them and are commonly discovered. [257][258][259] Researchers have found that epigenetic alterations, in addition to gene mutation, are critical in the development of tumors. Numerous studies have linked breast cancer to the epigenetic silencing of autosomal genes like RASSF1 at locus 3p21.31 260 ; NDRG1 at locus 8q24.22.…”
Section: Discussionmentioning
confidence: 99%
“…It is fascinating that 19 X‐linked TSGs that are connected to breast cancer have been discovered. DUSP9 , FLNA , GPC3 , RBBP7 , KDM6A , RBMX , FOXP3 , and EDA2R mutation patterns are among them and are commonly discovered 257–259 . Researchers have found that epigenetic alterations, in addition to gene mutation, are critical in the development of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The FOXP3 rs3761547 was selected because the FOXP3 rs3761547 polymorphisms was suggested as a male-specific risk factor in multiple sclerosis [25], or important markers to determine susceptibility and risk of diseases such as Crohn's disease [26] and interstitial lung disease (ILD) [27]. The rs3761548 was selected because it was suggested that the FOXP3 rs3761548 SNPs could affect the susceptibility to gastric adenocarcinoma (GA) and the serum IL-35, IL-10, and TGF-β concentrations [20], and the rs3761548 polymorphism of FOXP3 gene may provide as a risk factor in the development of breast cancer (BC) [28]. The rs3761549 was selected because the rs3761549 variants may play a role to protect against high-risk human papilloma virus (HR-HPV) and cervical cancer malignant lesions by down-regulating FOXP3 [18].…”
Section: Selection Of Foxp3 Snpsmentioning
confidence: 99%